Design, synthesis and photophysical properties of A-D-A-D-A small molecules for photovoltaic application. (October 2015) - Yan, Weibo; Zhang, Qian; Qin, Qingsong; Ye, Senyun; Lin, Yuanwei; Liu, Zhiwei; Bian, Zuqiang; Chen, Yongsheng; Huang, Chunhui
Abstract: A series of linear-conjugated small molecule compounds featured with the acceptor-donor-acceptor-donor-acceptor (A-D-A-D-A) structure were designed, synthesized and characterized. The films of the compounds showed a broad UV–Vis absorption range of 300–800 nm with high molar absorption coefficient of more than 1.0 × 10 4 cm −1 . Their hole-mobility can be as high as 1.0 × 10 −3 cm 2 V −1 s −1 . The compounds have a compatible HOMO energy level of −5.0 eV to PC71 BM and a high solubility up to 20 mg mL −1 in chloroform. Therefore, compounds can blend with PC71 BM in the chloroform and form an active layer for a photovoltaic cell device by spin-coating of the blend solution. A maximum power conversion efficiency of 3.2% was achieved with the DERH3TT solar cell device. These results indicate that the A-D-A-D-A small molecules with electron-withdrawing dyes as terminals are promising candidates for the high efficiency solution processed organic photovoltaic cells. Graphical abstract: Highlights: Five small molecules for photovoltaic cells are described by an A-D-A-D-A structure. These molecules possess broad absorption spectrum and high absorption coefficient. High hole-mobility and energy level of these donor molecules match with that of PCBM. The DERH3TT-based cells exhibited maximum PCE of 3.19%. These molecules based devices showed broad photoelectric response from 300 to 800 nm.